The The Role Of Supervision As A Strategy To Improve The Quality Of Islamic Education In Muhammadiyah 4 Zamzam Sukodono Sidoarjo : Peran Supervisi Sebagai Strategi Peningkatan Mutu Pendidikan Islam Di Sd Muhammadiyah 4 Zamzam Sukodono Sidoarjo - Ramadhan, Satrio Ryan; Wahyuni, Hana Catur (Indonesian Journal of Innovation Studies, 2026)
General Background Educational supervision operates as a fundamental instrument to monitor learning achievements and shape student character within Islamic primary institutions. Specific Background Implementation at SD Muhammadiyah 4 Zamzam Sukodono involves periodic administrative and academic evaluations conducted twice annually by school leadership. Knowledge Gap Existing literature lacks comprehensive insight into how collaborative supervisory frameworks specifically resolve internal coordination barriers and infrastructure constraints. Aims This study investigates the role of supervision as a strategic approach to improve educational quality and identifies supporting and inhibiting factors. Results Qualitative findings reveal that systematic supervision successfully upgraded curriculum management, learning processes, administrative services, and school infrastructure. Novelty The research demonstrates that leadership-driven collaborative supervision directly mitigates institutional constraints through structured planning, classroom observation, and reflective evaluation. Implications Educational institutions must integrate collaborative supervisory practices with enhanced stakeholder coordination to achieve optimal institutional standards and sustainable academic development. Key Findings Highlights Systematic supervision execution by school leadership significantly drives improvements across curriculum management, learning processes, and administrative services. Collaborative planning, classroom observation, and reflective evaluation serve as core mechanisms for maintaining educator professionalism. Insufficient coordination spaces and limited facility infrastructure represent primary internal obstacles to optimizing supervisory execution. Keywords : Educational Supervision, Islamic Education Quality, School Leadership Strategy, Collaborative Evaluation, Primary School Management